Critical Conceptualization of Women's Entrepreneurship: Reflections on the Turkish Entrepreneurship Ecosystem - Seçkin Halaç, Duygu; Samur Teraman, Seray Begüm (My University, 2022)
While women's entrepreneurship preserves its traditional entrepreneurial mission from a neo-liberal perspective, it has also been accepted as an essential tool in ensuring equality and empowering women with a gender perspective. It is seen that supranational institutions are trying to realize these two perspectives together, at least working in this direction. This study aims to conceptualize “women's entrepreneurship” and bring it to the agenda in Turkey form a gender perspective. Evaluating the literature on women's entrepreneurship from a historical perspective and examining the fundamental inequalities embedded in entrepreneurship, especially in a developing economy such as Turkey that still has structural gaps, is the study's main contribution.
Keywords: Gender Equality; Gender; Work-Life Balance; Social Role; Organization for Economic Co-operation and Development (OECD); Gender Gap; Social Constructivism; Female Entrepreneurship